Role Model Kepemimpinan Transformasional Berdasarkan 2 Raja-raja 18:1-8 pada Borneo Evangelical Mission Sarawak - Welly Sigo (Angelion, 2021)
The leadership factor greatly determines the progress and success of an organization. During the same period as the Borneo Evangelical Mission (BEM) Synod, which has reached 93 years this year. It was time for BEM to evaluate existing leadership, both related to institutionalization, administrative systems and service programs. This research is a qualitative research with historical and phenomenological analysis, which uses observation, documentation, and interview techniques. The data analysis model used is descriptive analysis using the perspective of Christian leadership to find a suitable model for future BEM leaders. The purpose of this study was to determine the role model of transformational leadership based on biblical principles taken from 2 Kings 18: 1-8 to become a role model for the leadership of BEM Sarawak, especially in every level at the central and regional levels. Of course this research will also indirectly impress the leadership in the rankings of local churches and ministries that are available in BEM Sarawak. This study aims to find the principles of biblical leadership practice, and to provide answers to biblical principles for leaders and congregations to continue to play an active role in the ministry through the opportunities God has given them. Practically the results of this research can help the leaders of BEM Sarawak to lead the congregation to mobilize all congregations to become involved as channels of God's love to this world.Faktor kepemimpinan sangat menentukan kemajuan dan keberhasilan sebuah organisasi. Selama kurun waktu bersamaan dengan usia Sinode Borneo Evangelical Mission (BEM) yang sudah mencapai 93 tahun pada tahun ini. Tiba masanya untuk BEM melakukan evaluasi terhadap kepemimpinan yang ada, baik yang berkaitan dengan pelembagaan, sistem administrasi dan program pelayanan. Penelitian ini merupakan penelitian kualitatif dengan analisis historis dan fenomenologi, yang menggunakan teknik observasi, dokumentasi, dan wawancara. Model analisis data yang digunakan ialah analisis deskriptif dengan menggunakan perspektif kepemimpinan Kristen untuk menemukan model yang sesuai bagi pemimpin BEM akan datang. Tujuan penelitian ini adalah untuk mengetahui Role Model kepemimpinan transformasional berdasarkan prinsip Alkitab yang diambil dari 2 Raja-Raja 18:1-8 menjadi role model bagi kepemimpinan BEM Sarawak khususnya di setiap peringkat di pusat dan daerah. Sudah tentu penelitian ini juga secara tidak langsung akan memberi kesan kepada kepemimpinan di peringkat gereja-gereja lokal dan bidang-bidang pelayanan yang sedia ada di dalam BEM Sarawak. Penelitian ini bertujuan menemukan prinsip-prinsip pelaksanaan kepemimpinan yang Alkitabiah, dan memberi jawaban terhadap prinsip Alkitabiah kepada pemimpin dan jemaat agar tetap berperan aktif di dalam pelayanan melalui kesempatan yang Tuhan anugerahkan. Secara praktis hasil penelitian ini dapat membantu para pemimpin BEM Sarawak untuk memimpin jemaat untuk mengerakkan semua jemaat untuk terlibat menjadi saluran kasih Allah kepada dunia ini.